Indeks Kerukunan Umat Beragama Kota Semarang Ditinjau dari Dimensi Moderasi Beragama - Sukestiyarno Sukestiyarno; Sugiyana Sugiyana; Muhammad Sulthon; Wuriningsih Wuriningsih; Hartutik Hartutik (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
This research measures the index of religious moderation in the city of Semarang and analyzes the dimensions of religious moderation that include 4 indicators of religious moderation, namely 1) national commitment, 2) tolerance, 3) anti-violence and 4) accommodative to local culture. Semarang is a city that has a plurality of religions as well as ethnic groups. This can actually be the main capital in regional development. The research method used in this study was an approach with quantitative descriptive statistics. The population of this study was Semarang people, with the number of 1,681,058 in 16 districts. The sampling technique was carried out by stratified random sampling where the representatives from each of the districts were taken. 611 people were selected as the research sample. The research focus was on the four indicators of religious moderation. Retrieval of data used a questionnaire. Data was processed descriptively. After conducting a field survey by FKUB Semarang City in 2021, the results obtained were that the religious moderation harmony index was 77.5 (very high). Furthermore, the index of the four indicators are national commitment, tolerance, anti-violence, adaptive to local culture respectively 70.23; 82.90; 77.93; 83,43. All the indexes have very good criteria, but the national commitment index is still high.